PENGUJIAN BAHAN ISOLASI KERAMIK TERHADAP TEGANGAN TEMBUS DENGAN MENGGUNAKAN ELEKTRODA BATANG - Hani, Slamet (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2014)
Various types of ceramic materials are mostly found in Indonesia which have different common properties, so lab experiments are needed to determine the natures of the breakdown voltages, capacities, and factors which determine the performance of each ceramic insulator. Type of ceramic tile studied were of diferent platinum, ceramic tile brands. The experiments sho that, the average breakdown voltage of ceramic platinum is 8.12kV, the room conditions during testing were 29.70C, 989mB air pressure and humidity 77%, while the average breakdown voltage of ceramic milan was 9.12kV, where condition during the test was 29.10C, 990 mB air pressure, relative humidity 79% and for brands essenza average breakdown voltage 39.68kV, under a testing temperature of 29.90C, pressure 989 mB air and 66% humidity. Of the three types the ceramic platinum brand was most easily penetrated by the voltage. This is do caused by the existing cavities in the ceramics and does not meet the standard ceramic or solid materials and most of them have the ability to withstand the breakdown voltage ceramic materials essenza brands.